A Brucellosis Disease Control Strategy for the Kakheti Region of the Country of Georgia: An Agent‐Based Model. (24th July 2013) - Havas, K. A.; Boone, R. B.; Hill, A. E.; Salman, M. D.
Summary Brucellosis has been reported in livestock and humans in the country of Georgia with Brucella melitensis as the most common species causing disease. Georgia lacked sufficient data to assess effectiveness of the various potential control measures utilizing a reliable population‐based simulation model of animal‐to‐human transmission of this infection. Therefore, an agent‐based model was built using data from previous studies to evaluate the effect of an animal‐level infection control programme on human incidence and sheep flock and cattle herd prevalence of brucellosis in the Kakheti region of Georgia. This model simulated the patterns of interaction of human–animal workers, sheep flocks and cattle herds with various infection control measures and returned population‐based data. The model simulates the use of control measures needed for herd and flock prevalence to fall below 2%. As per the model output, shepherds had the greatest disease reduction as a result of the infection control programme. Cattle had the greatest influence on the incidence of human disease. Control strategies should include all susceptible animal species, sheep and cattle, identify the species of brucellosis present in the cattle population and should be conducted at the municipality level. This approach can be considered as a model to other countries and regions when assessment of control strategies is needed but data are scattered.